SERVICE QUALITY STUDY ON CUSTOMER SATISFACTION AT KSP ASRI BONDOWOSO - Anam, Chairil; Qomariah, Nurul; Rusdiyanto, Rusdiyanto (Universitas Muhammadiyah Tangerang, 2024)
This research aims to determine the influence of service quality, namely tangible (physical evidence service), reliability (reliability service), responsiveness (response service), assurance (guarantee service) and empathy (empathetic service) on KSP Asri Bondowoso customer satisfaction. This type of research is quantitative causality research. The population in this study were all KSP Asri Bondowoso customers with a sample of 90 saving customers. Sampling was carried out using non-probability techniques. Data collection techniques were carried out using questionnaires. Data analysis was carried out using multiple regression analysis techniques. The research results show that tangible (physical evidence services), reliability (reliability services) and responsiveness (response services), assurance (guarantee services) and empathy (empathetic services) have a partially positive and significant effect on customer satisfaction